Nutritional risk, functional decline, and symptom burden in lung cancer: a study based on PG-SGA scores and biochemical data - Shen, Shasha; Xing, Shiyun; Shen, Tingting; Niu, Li; Tian, Xiaojing; Ma, Hu; Gou, Xiaoxia (Frontiers in Nutrition, 2025)
ObjectiveThis study aims to investigate the relationship between nutritional status and quality of life (QOL) in patients with lung cancer, analyze the clinical application of nutritional support, and explore its association with biochemical markers and physical function.MethodsA total of 270 hospitalized lung cancer patients were enrolled. Demographic characteristics, cancer staging, and treatment details were collected. Nutritional and functional status were assessed using the Patient-Generated Subjective Global Assessment (PG-SGA), Nutritional Risk Screening 2002 (NRS-2002), and Karnofsky Performance Status (KPS) scores. Quality of life was evaluated with the EORTC QLQ-C30 questionnaire. The relationships between nutritional status, blood biochemical markers, body composition, and quality of life were analyzed.ResultsAmong the 270 hospitalized lung cancer patients analyzed, 74.81% were male, and 80.74% were aged over 65 years. PG-SGA scores indicated that 38.89% of patients were at high nutritional risk (PG-SGA ≥ 9), and 77.04% had not received nutritional support. PG-SGA scores were significantly correlated with several biochemical indicators (e.g., prealbumin, total bilirubin, alanine aminotransferase, and lymphocyte count) and nutritional parameters (e.g., NRS-2002, KPS scores, body weight, and mid-upper arm circumference). Patients with higher PG-SGA scores had significantly lower scores in physical functioning, role functioning, emotional functioning, and social functioning, alongside more severe symptoms such as fatigue, nausea, and pain. Further analysis revealed a negative correlation between PG-SGA scores and overall health status (r = −0.687, p < 0.001) and positive correlations with symptoms such as fatigue, nausea, pain, and insomnia (r > 0.5, p < 0.001).ConclusionNutritional status significantly impacts the quality of life in patients with lung cancer. PG-SGA scores are strongly associated with patients’ functional abilities and symptom burden. Despite the low utilization of nutritional support, particularly in high-risk groups, improving nutritional interventions may effectively enhance functional status and quality of life in these patients.